Preparation of Alcoholic Beverages by Tribal Communities in the Indian Himalayan Region: A Review on Traditional and Ethnic Consideration - Rawat, Janhvi Mishra; Pandey, Shweta; Debbarma, Prasenjit; Rawat, Balwant (Frontiers in Sustainable Food Systems, 2021)
The Indian Himalayan Region (IHR) is the centre of the diverse food culture comprising fermented and non-fermented ethnic foods and alcoholic beverages. Diverse tribal communities in IHR (Uttarakhand, Himachal Pradesh, Jammu & Kashmir, Laddakh, Sikkim, Assam, Arunachal Pradesh, Manipur, Meghalaya and Tripura) have been long known for their rich culture and food habits. Having strong ritual importance among the ethnic people of the IHR, alcoholic beverages are being consumed in various cultural, social and religious events for ages. Consumption of in-house prepared alcoholic beverage is the socio-cultural tradition in India as well as across the globe. The processes and ingredients involved in alcoholic beverage preparations vary with raw material availability in different regions. The majority of the fermented drinks are cereal-based with a significant proportion of various plants and fruits as the main raw material, making a beverage more unique in taste. Some plant ingredients used for traditional alcoholic beverages have potential nutraceutical as well as therapeutic properties that are well documented. These properties could constitute an additional economic value for traditional alcoholic beverages commercialization, which in turn could promote the local rural economy. Till now such beverages have only received marginal attention by ethnobotanists and few studies concern traditional fermented beverages in the IHR. In this view, the current review focused on preparation, diversity, cultural and economic significance and health benefits of ethnic beverages used by tribal communities in the IHR.